Implementasi Gaya Narasi Ekspositoris dalam Penyusunan Naskah Video Feature “Menyemai Harapan, Memanen Kebersamaan” - Decky Hastri Putri; Trie Damayanti; Nurmaya Prahatmaja (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The video feature "Menyemai Harapan, Memanen Kebersamaan" highlights urban agriculture as a solution to land limitations and food security challenges, while also encouraging a sustainable lifestyle and social interaction through the Community Supported Agriculture (CSA) system. This final project aims to design an informative and systematic expository narrative style feature video script. The creation process includes pre-production, production, and post-production, with an emphasis on research, a three-act structure, and writing dialogue and visual descriptions. The result is a video about nine minutes long that is able to explain the concept and practice of urban agriculture. The expository narrative style has proven effective in conveying complex information clearly and interestingly, and encouraging community participation.